Sirtuin 1 and Skin: Implications in Intrinsic and Extrinsic Aging—A Systematic Review - Angelika Bielach-Bazyluk; Edyta Zbroch; Hanna Mysliwiec; Alicja Rydzewska-Rosolowska; Katarzyna Kakareko; Iwona Flisiak; Tomasz Hryszko (Cells, 2021)
Skin, as the outermost organ of the body, is constantly exposed to both intrinsic and extrinsic causative factors of aging. Intrinsic aging is related to compromised cellular proliferative capacity, and may be accelerated by harmful environmental influences with the greatest significance of ultraviolet radiation exposure, contributing not only to premature aging, but also to skin carcinogenesis. The overall skin cancer burden and steadily increasing global antiaging market provide an incentive for searching novel targets to improve skin resistance against external injury. Sirtuin 1, initially linked to extension of yeast and rodent lifespan, plays a key role in epigenetic modification of proteins, histones, and chromatin by which regulates the expression of genes implicated in the oxidative stress response and apoptosis. The spectrum of cellular pathways regulated by sirtuin 1 suggests its beneficial impact on skin aging. However, the data on its role in carcinogenesis remains controversial. The aim of this review was to discuss the relevance of sirtuin 1 in skin aging, in the context of intrinsic factors, related to genetic premature aging syndromes, as well as extrinsic modifiable ones, with the assessment of its future application. PubMed were searched from inception to 4 January 2021 for relevant papers with further search carried out on ClinicalTrials.gov. The systematic review included 46 eligible original articles. The evidence from numerous studies proves sirtuin 1 significance in both chronological and premature aging as well as its dual role in cancer development. Several botanical compounds hold the potential to improve skin aging symptoms.